P79 Prevention of the "airway to heaven": training for final year medical students on acute airway and tracheostomy management. (5th November 2017) - Htyn, M; Gokhale, O; Stafford, N
Abstract : Background: Junior doctors are often the first team members to assess and treat clinically deteriorating patients in hospital. Despite this, many do not feel confident in their ability to manage a patient's airway during a cardiac arrest. 1 Furthermore, studies demonstrate that junior doctors have insufficient airway skills for resuscitation purposes. 2 This project aimed to provide airway training to University of X medical students on their final clinical placement at AB Academy preparing to become doctors in August 2017. Methodology: 30 Final Year medical students were divided into five groups. Each group underwent a training session between 28th February and 15th March 2017. Students completed anonymised pre-course questionnaires (Likert scale and free text boxes) and short written assessments (total mark 20). They received an interactive Airway Management tutorial. Students then rotated in pairs through 3 workshop stations: Basic Airway Manoeuvres, Airway Adjuncts, Supraglottic Airway Devices. A tutorial on emergency management of tracheostomies followed. Formative assessment was incorporated into every stage of the session. Upon starting the post-course test and questionnaire, the students were called to an emergency (a surprise simulation), which included progression to cardiac arrest. Following a debrief session, the questionnaires were completed. The questionnaires underwent thematic analysis. Mean, median and modal scores were calculated for the Likert responses. A paired t-test was utilised for the test scores. Results: The mean pre and post-course test scores were 11.5 and 16.4 respectively. There was a statistically significant improvement in the scores (p<0.00001). The pre-course questionnaire demonstrated that students would not have felt confident to manage a patient's airway in an emergency, did "not feel senior enough", and would be concerned about causing harm to the patient. They were particularly worried about managing a patient with a tracheostomy, stating that they "wouldn't know where to start". All the students found the session beneficial, especially as it was "hands-on". They felt that it would be a positive addition to the curriculum. Conclusions: The students' knowledge and confidence increased post-training. The different teaching methods enabled students to consolidate and apply their knowledge and skills with an appreciation of the context. We hope that as junior doctors, putting this into practice will contribute to improved patient outcomes. This work serves as a pilot project for the modification of the airway training component of the University curriculum. Discussions with the lead Consultant Anaesthetist for the Perioperative Care module have been met with enthusiasm. References: . Khoyratty S, Crossland C, Bevan A, Htyn M, Mathers E, Hewson D, Sudan S, Desai K. Junior doctors' attitudes to their own airway skills; A questionnaire survey . Poster Presentation at Group of Anaesthetists in Training Annual Scientific Meeting 2011. . Kidner K, Laurence AS. Basic airway management by junior doctors: Assessment and training on human apnoeic subjects in the anaesthetic room. Anaesthesia2006;61(8):739–42.